2005
DOI: 10.1016/j.febslet.2005.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and multilocus sequence typing of 145 strains of SARS‐CoV

Abstract: In this study, we have identified 876 polymorphism sites in 145 complete or partial genomes of SARS-CoV available in the NCBI GenBank. One hundred and seventyfour of these sites existed in two or more SARS-CoV genome sequences. According to the sequence polymorphism, all SARS-CoVs can be divided into three groups: (I) group 1, animal-origin viruses (such as SARS-CoV SZ1, SZ3, SZ13 and SZ16); (II) group 2, all viruses with clinical origin during first epidemic; and (III) group 3, SARS-CoV GD03T0013. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Interestingly, the clustering of patients with different patterns of variations in ORF8 region was correlated with the different phases of the epidemic. These findings were subsequently verified by researchers who studied the SARS-CoV isolated in different countries (Chiu et al, 2005;Lan et al, 2005;Qin et al, 2003;Wang et al, 2004Wang et al, , 2005.…”
Section: Introductionmentioning
confidence: 70%
“…Interestingly, the clustering of patients with different patterns of variations in ORF8 region was correlated with the different phases of the epidemic. These findings were subsequently verified by researchers who studied the SARS-CoV isolated in different countries (Chiu et al, 2005;Lan et al, 2005;Qin et al, 2003;Wang et al, 2004Wang et al, , 2005.…”
Section: Introductionmentioning
confidence: 70%
“…GD03T0013 is closely related to SARS‐CoV isolated from civets served in a restaurant in Guangzhou, China in late 2003 and early 2004. No epidemiological data link the GD03T0013 human case to exposure to laboratory isolates of SARS‐CoV (Wang et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have documented various SNVs in the SARS-CoV genome, with some even proposing them as the basis for a genotypic classification (Poon et al, 2005a,b;Ruan et al, 2003;Tsui et al, 2003;Wang et al, 2005;Yeh et al, 2004). In this study, the SNV G23220T that was found in all of the patients (56/56, 100%) has been reported elsewhere (Yeh et al, 2004), though the functional significance of this is presently uncertain.…”
Section: Discussionmentioning
confidence: 52%
“…The second, less frequently found SNV (C25114T) present in 17/56 (30.4%) of these S-gene sequences has also been found in four sequences from Guangdong (GUAN LC2, AY394999; GUAN LC3, AY395000; GUAN LC4, AY395001; GUAN LC5, AY395002, but not in GUAN LC1, AY394998), of which GUAN LC3 and GUAN LC5 have been previously reported by Wang et al (2005). The 17 CUHK S-gene sequences containing this polymorphism all occur in samples collected towards the end of the SARS outbreaks in Hong Kong (from 4 April to 31 May 2003).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation